Strategi Pengembangan Usaha Kerajinan Anyaman Lidi Nipah (Studi Kasus: Kelompok Bungong Chirih) Di Desa Matang Gleum Kecamatan Peureulak Kabupaten Aceh Timur - Aflan, Muhammad; ., Supristiwendi; Basriwijaya, Kiagus M. Zain (Prodi Agroteknologi dan Agribisnis - Universitas Kristen Wira Wacana Sumba, 2023)
The objectives of this study are to identify internal and external factors for the development of the Lidi Nipah Woven Handicraft business in the Bungong Chirih group and analyze the business development strategy of Lidi Nipah Woven Crafts in the Bungong Chirih group. This research was conducted in Matang Gleum Village, Peureulak District, East Aceh Regency. The method used is a case study. The sample in this study was the business owner of the Bungong Chirih group. Respondents in this study were identified from 5 key figures. The analysis methods used are SWOT and QSPM. The results showed that alternative strategies that can be applied in developing a business based on the SWOT matrix get 8 alternative strategies, namely there are two SO Strategies, two ST Strategies, two WO Strategies, and two WT Strategies. Meanwhile, the priority strategy that can be applied in developing the Lidi Nipah Woven handicraft business in the Bungong Chirih Group in Matang Gleum Village, Peureulak District, East Aceh Regency based on QSPM analysis, results were obtained utilizing good product quality and continuing to produce products according to consumer demand in order to continue to be able to lead the market and enter the regional market, Maximizing internet media as a promotional medium and as a marketing medium so that products can be more widely known and reached.